2021
DOI: 10.21608/puj.2021.96310.1134
|View full text |Cite
|
Sign up to set email alerts
|

The impact of H. pylori and/or T. gondii infection on recurrence of gastritis and gastric ulcer

Abstract: Possession of a well-known virulence factor as the cytotoxin-associated gene A (cag-A), allows some H. pylori strains to cause more severe inflammation and widespread atrophy in gastric mucosa than those lacking this gene [7,8] . Early immunological detection of cag-A protein just after H. pylori

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
1
2
1
Order By: Relevance
“…However, when examining the relationship between the titer of Toxoplasma antibodies and the stage of chronic inflammation ( r = 0.167, P = 0.395) as well as the degree of activity ( r = 0.103, P = 0.600), no statistically significant association was seen for either variable. The findings of this study were incongruent with the research conducted by Ghazy et al [ 16 ] since their study demonstrated a positive correlation between the severity of gastritis cases and elevated levels of serum anti- Toxoplasma IgG.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, when examining the relationship between the titer of Toxoplasma antibodies and the stage of chronic inflammation ( r = 0.167, P = 0.395) as well as the degree of activity ( r = 0.103, P = 0.600), no statistically significant association was seen for either variable. The findings of this study were incongruent with the research conducted by Ghazy et al [ 16 ] since their study demonstrated a positive correlation between the severity of gastritis cases and elevated levels of serum anti- Toxoplasma IgG.…”
Section: Discussioncontrasting
confidence: 99%
“…The present study’s findings indicate that among a cohort of 31 individuals who were simultaneously infected with both H. pylori and T. gondii , a substantial majority (80.6%) experienced gastritis of moderate to severe intensity. The results were in line with Ghazy et al [ 16 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is frequently acquired during childhood and persists throughout the patient's life (Román‐Román et al, 2019). Persistent colonization of the gastric mucosa may progress to peptic ulcer disease (PUD) and/or gastric cancer due to chronic inflammation, mucosal damage, ulceration and transformation of the gastric mucosa to metaplastic or dysplastic epithelial (Ghazy et al, 2021; Román‐Román et al, 2019; Ryberg et al, 2013; Saribas et al, 2020).…”
Section: Discussionmentioning
confidence: 99%